(untitled) (Zoological Records and Reviews, 2022)
Eastern India – encompassing the states of West Bengal, Odisha, Jharkhand, and Bihar – represents a biogeographically complex region at the confluence of the Indo-Gangetic Plain, the Eastern Ghats, and the transition zone towards the northeastern Indian subregion. Despite this diversity, the chiropteran fauna of eastern India remains taxonomically incomplete, with numerous nomenclatural issues unresolved and distributional data fragmented across scattered literature. This study presents a comprehensive species composition and taxonomic assessment of bats from eastern India based on field surveys at 78 localities conducted between 2018 and 2021, supplemented by examination of museum specimens and molecular analysis of mitochondrial cytochrome b sequences from 284 individuals. We document 64 bat species belonging to 8 families and 32 genera, including 6 new state records and 2 candidate new species. The families Vespertilionidae (28 species) and Rhinolophidae (14 species) dominate the regional fauna. Molecular phylogenetic analysis resolves long-standing taxonomic uncertainty in the Rhinolophus trifoliatus complex and confirms the species status of Kerivoula picta populations from Odisha forests, previously treated as conspecific with Himalayan populations. Updated echolocation parameters, morphometric diagnoses, and revised distribution maps are provided for all documented species. Eighteen species are assessed as IUCN Threatened or Near Threatened. Roost site loss, deforestation, and cave disturbance are identified as primary threats to bat conservation in eastern India.